Video-based perceptual training as a method to improve reactive agility performance in rugby union players - Engelbrecht, L.; Terblanche, E.; Welman, K. E. (International Journal of Sports Science & Coaching, 2016)
This study investigated the effectiveness of rugby-specific video-based perceptual training on the speed and agility of club-level rugby union players. Twenty-six players were randomly divided into either a video-based, field-based or conventional training group. For six weeks, the video-based and field-based groups performed agility training twice a week in addition to their regular rugby training, while the control group was restricted to regular rugby training. Speed, reactive agility and change of direction speed were tested pre- and post-intervention, and after a six-week retention period. Results revealed that both video- and field-based training were almost certainly more beneficial (13% and 17%, respectively) to improve reactive agility compared to conventional rugby training alone. In addition, both intervention groups maintained their reactive agility improvements following the retention period. Consequently, video-based training, likely because of a perceptual component, could be used as an alternative training method to improve reactive agility. ABSTRACT FROM AUTHOR